2021
DOI: 10.3390/metabo11120845
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Bile Acid Metabolomics in the Follicular Fluid of PCOS Patients

Abstract: Polycystic ovary syndrome (PCOS) is a complex heterogeneous endocrine disease affected by genetic and environmental factors. In this manuscript, we aimed to describe the composition of bile acid metabolomics in the follicular fluid (FF) of PCOS. The FF was collected from 31 control patients and 35 PCOS patients diagnosed according to the Rotterdam diagnostic criteria. The Bile Acid Assay Kit and ultra-performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) were used in this study to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Some studies reported that the decreased level of SCFA might be related to the development of insulin-resistant ( 58 ), which plays an important role in the development of PCOS ( Figure 2 ). Besides, it has been suggested that bile acid is related to microbiome in PCOS women ( 59 ). Gut microbiota could regulate bile acid metabolism including in synthesis, metabolism, and reabsorption of bile acids, through vitamin D receptor and G protein-coupled receptor ( 60 ).…”
Section: Relation Of Microbiota and Pcosmentioning
confidence: 99%
“…Some studies reported that the decreased level of SCFA might be related to the development of insulin-resistant ( 58 ), which plays an important role in the development of PCOS ( Figure 2 ). Besides, it has been suggested that bile acid is related to microbiome in PCOS women ( 59 ). Gut microbiota could regulate bile acid metabolism including in synthesis, metabolism, and reabsorption of bile acids, through vitamin D receptor and G protein-coupled receptor ( 60 ).…”
Section: Relation Of Microbiota and Pcosmentioning
confidence: 99%
“…Some of the characteristics of these techniques are specified in Table 1 . Some studies have also resorted to ultra-high performance liquid chromatography coupled with mass spectrometry (UHPLC-MS) [ 122 ], ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS) [ 76 ], multiple reaction monitoring (MRM)-profiling [ 123 ], and different types of immunoassays [ 33 , 124 , 125 , 126 ].…”
Section: Metabolomics In Pcosmentioning
confidence: 99%
“…Until today, both the subsequent etiology and pathophysiology of PCOS remain unclear. To reduce the psychological and social pressures that come with this pathology, several studies were conducted to facilitate the diagnosis and treatments [ 1 , 76 ]. Patients with PCOS that undergo assisted reproductive techniques (ART) might present a poor to exaggerated response, low oocyte quality, ovarian hyperstimulation syndrome, as well as changes in the FF metabolites pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a gut microbial community, BA moieties would have remained a conservative set of molecules. Bacterial enzymatic modifications in the gut lumen are responsible for the huge diversity of BAs detected regionally in the liver, the gut, the systemic circulation (Staley et al., 2017) and even the brain (Zheng et al., 2016), breast milk (Forsyth et al., 1983) and ovarian follicles (Yang et al., 2021). Often, secondary bile acids are more potent agonists for BA receptors (Ridlon et al., 2016).…”
Section: Contextmentioning
confidence: 99%